Comparative Metabolomic and Transcriptomic Analyses Uncover Variation in Pigment Accumulation Profiles in Alpinia hainanensis Bracts - Tong Zhao; Qianxia Yu; Huanfang Liu; Zehong Wei (Horticulturae)
Alpinia hainanensis is a famous flowering herbaceous plant with valuable ornamental value that is distinguished by its brightly colored labellum. A. hainanensis ‘Shengzhen’ has been identified to possess a novel ornamental feature: its inflorescence is adorned with charming pink bracts. Although flavonoids are recognized as the primary pigments that color most flowers, the role of their metabolic pathways in shaping the bract color of A. hainanensis ‘Shengzhen’ has not yet been fully explored. This research performed transcriptomic and metabolomic analyses on the floral bracts of both wild-type (white bract) and ‘Shengzhen’ cultivar (pink bract) of A. hainanensis. The results identified 565 flavonoid metabolites, including 19 anthocyanins. The ‘Shengzhen’ cultivar showed a higher accumulation of 17 anthocyanins (seven cyanidins, two delphinidins, one pelargonidin, three peonidins, and four petunidins) compared to the wild type. A combined transcriptomic and metabonomic investigation revealed significant links between four differentially expressed genes and seven anthocyanins. The key genes responsible for flavonoid and anthocyanin synthesis, such as AhPAL, AhC4H, AhCHI, AhF3H, AhDFR, AhFLS, and AhF3′5′H, were further analyzed to explain the differences in pigmentation. This study offers a fresh perspective on anthocyanin accumulation in Alpinia, paving the way for future flower color breeding efforts in the genus.